Penerapan Pendidikan Karakter Melalui Metode Bercerita Pada Anak Usia Dini di Tk Gmim Damai Rasi - Olga Evy Marelyne Sumual (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to improve the character of early childhood through the storytelling method. This research was conducted using Classroom Action Research (CAR), which refers to the research design proposed by Kemmis and Mc Taggart, consisting of 4 steps, namely: 1. Planning, 2. Action, 3. Observation, 4. Reflection. The research subjects were GMIM Damai Rasi Kindergarten students. Data collection techniques based on observation. The data analysis technique was carried out by comparing the results of learning achievements in each cycle. The learning outcomes obtained in the first cycle only reached 59.72% while in the second cycle the student learning outcomes reached 91.66%. Based on the results of research and discussion, it can be concluded that the use of the storytelling method can improve the character of early childhood in GMIM Damai Rasi Kindergarten. To further develop children's character and character education, students and teachers are advised to use the storytelling method.